REPRODUCTIVE ACTIVITY AND VOCALIZATIONS OF LEPTODACTYLUS LABYRINTHICUS (ANURA: LEPTODACTYLIDAE) IN SOUTHEASTERN BRAZIL. - Juliana Zina (Biota Neotropica, 2005)
Vocalizations and reproductive activity of two Leptodactylus labyrinthicus populations were studied from Jun/2001 to Feb/2003 in the State of São Paulo, Brazil. Observations began at dusk and ended around 2300 h. Occasionally individuals were monitored throughout the night. Data on reproductive period, calling sites, adult snout-vent length (SVL), oviposition sites, and oviposition period was collected. Leptodactylus labyrinthicus had an extended breeding period associated mainly with rainfall. Males called from the edge of temporary or permanent ponds, began vocalization activity at dusk, and finished around 2300 or 2400h. During the peak of the vocalization period (Dec- Jan), calling activity could extend up to 0400 or 0500h. Three types of vocalizations associated with reproduction were recorded: advertisement call, territorial call, and courtship call. The advertisement call was the most common vocalization. Males and females showed no sexual dimorphism in SVL. However, the males of one population were significantly larger than those of the other population studied. This fact could be explained by frog-hunting in one of the areas, which could wipe out the larger males of the population. Foam nests were recorded mainly in Oct-Nov 2001/2002 in depressions at the edge of temporary ponds, always protected by vegetation. A mean of 6.5% of the eggs present in the foam were fertilized and the other 93.5% possibly are used as a food source by the tadpoles. Mean diameter of the foam nest was 25.4 cm and mean height was 11.4 cm.